2014
DOI: 10.1016/j.nbd.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolyl-hydroxylase inhibition and chronic intermittent hypoxia on synaptic transmission and plasticity in the rat CA1 and dentate gyrus

Abstract: Publication informationNeurobiology of Disease, 62 (February 2014): 8-17 Publisher Elsevier Item record/more information http://hdl.handle.net/10197/4791 Publisher's statementThis is the author's version of a work that was accepted for publication in Neurobiology of Disease. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…We and other investigators had previously demonstrated that hippocampal long-term synaptic plasticity is impaired after 7-14 days of IH treatments (60,63), a phenomenon that may underlie memory impairment in OSA subjects. To test whether ER stress plays a direct role in this process, we performed two sets of experiments.…”
Section: Ih-induced Er Stress Impairs Hippocampal Synaptic Plasticitymentioning
confidence: 76%
“…We and other investigators had previously demonstrated that hippocampal long-term synaptic plasticity is impaired after 7-14 days of IH treatments (60,63), a phenomenon that may underlie memory impairment in OSA subjects. To test whether ER stress plays a direct role in this process, we performed two sets of experiments.…”
Section: Ih-induced Er Stress Impairs Hippocampal Synaptic Plasticitymentioning
confidence: 76%
“…Employing pharmacological means or IH to enhance HIF1a in the hippocampus correlated with the 294 suppression of LTP in area CA1 (Wall et al, 2014). Similarly, oxidative stress has been implicated as a 295 significant factor that could influence neurophysiological and behavioral outcomes in response to IH (Xu et al, 296 2004).…”
Section: Results: 185 186mentioning
confidence: 99%
“…These impairments include learning and memory deficits (Jackson et al, 2011), difficulties in attention (Beebe and Gozal, 2002), and emotional dysregulation (Schröder and O'Hara, 2005). Although neuroimaging studies suggest that multiple brain regions are impacted by sleep apnea, the hippocampal formation is frequently identified as a site of injury in this condition (Morrell et al, 2003;Castronovo et al, 2009;Canessa et al, 2011;Torelli et al, 2011;Cha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%